Association of High Body Mass Index in Early Life With the Development of Colorectal Cancer - Nian Wu BM; Yangyang Chen MM; Guosheng Li MM (Cancer Control, 2024)
Colorectal cancer (CRC) is one of the most common malignant tumors of the digestive tract. In recent years, the age at which CRC is diagnosed has been trending younger on a global scale. Obesity, as a worldwide epidemic, is on the rise in most countries due to changes in dietary habits and lifestyles. Concurrently, with increased screening efforts and growing public awareness of health, the incidence of CRC in older adults is gradually declining, while the incidence in younger and middle-aged individuals is steadily increasing. This seems to indicate a strong association between overweight and obesity and a younger age of colorectal cancer diagnosis. Currently, with advancements in research on the relationship between early life (childhood and adolescence) body weight and CRC, new insights have been gained regarding the role of high BMI (overweight and obesity) in the occurrence and development of CRC, as well as its impact at different early life stages. Adolescence appears to be a particularly critical period. Therefore, this review will summarize the relationship between early life high BMI and CRC, aiming to provide a reference for clinical and basic research as well as CRC prevention. Significance This study on the relationship between early life high BMI and the development of CRC reveals the role of high BMI during childhood and adolescence in the occurrence and progression of CRC. It suggests the importance of restoring normal weight or reducing weight in individuals with high BMI early in life for the prevention of colorectal cancer.